Angina in Coronary Artery Disease Patients With and Without Diabetes: US National Health and Nutrition Examination Survey 2001–2010. Issue 1 (22nd December 2015) - Hui, Gavin; Koch, Bruce; Calara, Federico; Wong, Nathan D.
ABSTRACT: Background: Angina pectoris (AP) is common in coronary artery disease (CAD), but whether those with diabetes mellitus (DM) experience AP as often as those without DM is unclear. Hypothesis: AP prevalence is similar in those with vs without DM in a community sample with CAD. Methods: In adults with CAD in the US NHANES 2001–2010, AP was determined by self‐report and Rose questionnaire and compared by DM status. Physical functioning and medication use were also evaluated. Results: Of 1957 adults with CAD, 619 (28.2%) had DM. Prevalence of AP was similar in those with vs without DM (48.9% vs 46.3%; P = 0.38). There was a trend toward more severe AP in those with glycated hemoglobin ≥7% (50.4%) vs <7% (27.1%; P = 0.09). Adjusted logistic regression showed a similar odds of AP (1.06, 95% CI: 0.84‐1.33) in those with vs without DM, although among DM, a 2‐fold greater odds of AP in women vs men. Physical functioning was worse in those with vs without AP overall (score of 25.9 vs 24.3; P < 0.001) and further diminished within those with comorbid DM (26.7 vs 24.0; P < 0.001). Among those with AP, those with vs without DM were more likely on β‐blockers, statins, angiotensin‐converting enzyme inhibitors, and antiplatelet therapy. Conclusions: AP in CAD patients is similar among those with vs without DM, despite greater use of evidence‐based therapies in DM patients. Greater physical limitations exist in those with vs without AP, and further diminish with comorbid DM.